An inventory model on the impact of green investment with deteriorating items and planned back orders for economic efficiency and environmental sustainability - R, Vinodini; W, Ritha; Nagapan, Sasitharan (The Scientific Temper, 2025)
Green investment emphasis allocating capital for the industries and research works that promote environmental sustainability and reduce GHG (Greenhouse gas) emissions. It holds up the energy consumption, toxic pollution and the sustainable environment. This research examines the impact of green investment in the inventory model for deteriorating items with planned backorders to balance the economic efficiency and the environmental sustainability. The items are deteriorating at a natural decay process and their rate is proportional to the inventory level per unit time. It leads to the level of inventory. Back ordering happens when inventory is null and it will deliver after production takes place in the industries. The purpose of this framework is to create a green inventory mathematical model for reducing the total cost and carbon (CO2) emissions.